Novel Additives for Ni Electroplating that Eliminate Wastewater Production - Gezerman, Ahmet Ozan; Corbacioglu, Burcu Didem (CHEM SOC PAKISTAN, 2016)
The focus of this study is to improve the physical properties of electroplated Ni films, such as corrosion resistance, electrical resistivity, plating thickness, and adhesion force. The organic additives 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and thioglycolic acid were used in the electroplating bath for this purpose. The resulting Ni films were characterized by spectrophotometry, electron microscopy, and hardness tests. The implications for wastewater production associated with Ni plating are discussed within the context of these organic additives.
Keywords: Electroplated Ni; 2-mercaptobenzimidazole; 2-mercaptobenzothiazole; Thioglycolic acid; MAGNETIC-PROPERTIES; NICKEL; COATINGS; ALLOY; ACETYLACETONATE; BRIGHTENER; INTERLAYER; GOLD; Chemistry